Stress and strain analysis using Autodesk Inventor software in soil-cement brick (Research, Society and Development, 2021)
The computational analysis of materials is fundamental for a better understanding of their physical and mechanical properties, achieving more results in a shorter time. It is a cheaper, non-destructive, practical way, and easily adaptable to various types of models and physical influences. This study has the objective of ascertaining the stress and strain analysis in soil-cement brick through the Autodesk Inventor Professional software, which uses the finite element method. Three models of brick were made: two holes, monoblock, and groove, which are the most commonly used shapes. To the two holes model, the maximum first principal stress observed was 1.464x10-1 MPa and the third principal stress was 5.4x10-3 MPa, presenting an insignificant strain of 1.037x10-3 mm. In the monoblock model, the maximum first principal stress was 4.606x10-1 MPa, and the third principal stress was 1.19x10-2 MPa, presenting a strain of 1.611x10-3 mm.  The groove model presented the maximum first principal stress at 3.263x10-1 MPa and for the third principal stress was 9.1x10-3 MPa, respectively, presenting a strain of 3.344x10-3 mm. It can also be observed that the models have stress concentrating regions in the sharp edges and notches of the part. Among the three models studied, the one that presented the most favorable stress-strain conditions was the two-hole model. Since it has a larger contact area, the load applied to it was better distributed, presenting higher resistance than the other models with a smaller contact area.